Patient satisfaction among adult patients attending outpatient department of Klinik Kesihatan Greentown Ipoh, 2017 - Kharie, Mohamad Fadli (2017)
Introduction: Klinik Kesihatan Greentown is a healthcare clinic, which caters up to 1000 patient attendances a day that covers up to 39564 populations. Several initiatives have been initiated to meet public expectation and to improve their satisfaction towards the healthcare services, yet Klinik Kesihatan Greentown still receives complaints and dissatisfaction among the patients. This study aims to assess the patient satisfaction among adult patients who attend outpatient department of the clinic.